SEMINATURAL SILVICULTURE IN SOUTHWEST GERMANY - Spathelf, Peter (2000)
A brief historical overview shows the mainstream development pattern in German silviculture and outlines the adjacent role of seminatural (naturally-oriented) silviculture. The rationale for seminatural silviculture is discussed with reference to its ecological and economical aspects. Elements of seminatural silviculture of the Baden-Württemberg-concept are introduced. This concept is not purely a preservation strategy, but recognizes the importance of timber production. Some aspects of selection forest, which is a special case of uneven-aged forest with a long tradition in Southwest Germany, are discussed. As there are still a lot of even-aged (pure) forests in Southwest Germany, transformation strategies towards uneven-aged mixed forests are shown with the aid of some examples. Criteria and indicators for seminatural silviculture which have to be developed on a regional or local scale, can be used as a basis for establishing a certification process for Southwest German forests. Seminatural silviculture is suited as a rational and  intergrating  silvicultural     system      to     fulfill     future     requirements     on     forests     in    a    dynamically changing world.